Effect of using garlic oil on the production and composition of milk and some blood characteristics of Awassi Ewes - Ali, Wissam Jasim Mohammed; mohammed, Amar raeed; Ahmad, Wassem Khalid (Journal of agricultural, environmental and veterinary sciences, 2021)
This study was conducted in Beibocket area (8Km north of Mosul city) for the period 12-2-2019 to 13-4-2019. Fifteen Awassi ewes, with average 43.48 kg. aged (2-4years) is divided into three equal groups, (five ewes per group). Three groups were, feed relied on grazing fully. The first group was the control, the second group was given capsules 2 ml garlic oil/ewe/day. and the third group was given capsules of 4 ml garlic oil /ewe/day, respectively. The third group showed a significant increase (p
Keywords: Awassi Sheep; Blood Characteristics; Garlic oil; Milk Production